Mangrove Planting Program as an Effort to Prevent Coastal Abrasion and Preserve Coastal Ecosystems at Ujong Blang Beach, Lhokseumawe City - Salsabilla, Icha (Journal of Agricultural Economy and Technology Development, 2026)
Coastal abrasion problems frequently occur in coastal areas, where phenomena such as climate change and full moon phases serve as the primary triggers for elevated sea surface waves, ultimately leading to abrasion. Coastal abrasion refers to the shrinkage of the shoreline due to tidal sea level rise. Coastal abrasion causes an annual shoreline shrinkage of 5 meters. Elevated wave heights significantly impact the sustainability of the surrounding coastal environment. This study aims to evaluate the effectiveness of mangrove planting programs as a measure to prevent abrasion and preserve coastal ecosystems using a qualitative descriptive approach. The methods employed include field surveys, interviews with local communities and traders, as well as direct planting of 20 mangrove seedlings at 40 cm spacing and 5-8 cm depth in moist muddy areas. The results show that mangrove planting at Ujong Blang Beach was successfully carried out through collaboration between students and local communities, with the potential to dampen up to 70% of wave energy and stabilize sediments. The implications include environmental protection, improved economic welfare for surrounding communities, and recommendations for sustainable programs.